Circulating oxysterols and prognosis among women with a breast cancer diagnosis: results from the MARIE patient cohort - Decker, Nina Sophia; Johnson, Theron S.; Vey, Johannes; Le Cornet, Charlotte; Behrens, Sabine; Obi, Nadia; Kaaks, Rudolf; Chang-Claude, Jenny; Turzanski Fortner, Renée (BMC medicine, 2023)
Breast cancer is the most commonly diagnosed cancer in women worldwide, and underlying mechanistic pathways associated with breast cancer-specific and non-breast cancer-related deaths are of importance. Emerging evidence suggests a role of oxysterols, derivates of cholesterol, in multiple chronic diseases including breast cancer and coronary artery diseases. However, associations between oxysterols and survival have been minimally studied in women diagnosed with breast cancer. In this large breast cancer patient cohort, we evaluated associations between a panel of circulating oxysterols and mortality and recurrence outcomes.